A brief introduction to black holes - Fabiano, Nicola (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: Starting from general relativity, black hole gen- eration and effects are investigated. Method: Einstein’s equation and its Schwarzschild solution are employed to study black holes. Quantum mechanics is used to obtain Hawking’s radiation. Results: Black holes are actually not completely black - they radiate energy during their lifetime. Conclusions: Black holes could evaporate and this effect is observable if their mass is sufficiently small. Their entropy scales differently with respect to their mass from that of other objects in thermodynamics.